The Role of Immunotherapy in Hepatocellular Carcinoma (HCC) - Nurhayani Fatimah; Vesri Yoga; Arnelis -; Saptino Miro (The Indonesian Society for Digestive Endoscopy, 2026)
Hepatocellular carcinoma (HCC) is an aggressive primary liver malignancy with a historically poor prognosis and limited treatment options. It accounts for approximately 75–85% of all liver cancer cases worldwide, with an estimated global incidence of about 9.5 per 100,000 person-years. According to GLOBOCAN 2022, the liver cancer mortality-to-incidence ratio in Indonesia is 0.99, indicating that nearly all patients diagnosed with HCC die from the disease. Systemic therapy, primarily sorafenib, a targeted therapy approved since 2007, has long been the mainstay for advanced cases, but it offers limited clinical benefit. In recent years, immunotherapy, particularly immune checkpoint inhibitors (ICIs), has significantly altered the therapeutic approach to HCC. These agents function by inhibiting regulatory pathways such as PD-1/PD-L1 and CTLA-4, thereby enhancing immune-mediated tumor clearance. Clinical trials, such as IMbrave150, have shown that combining atezolizumab and bevacizumab leads to notable improvements in both overall and progression-free survival compared to sorafenib, resulting in its approval as a first-line treatment. Similarly, combinations like durvalumab with tremelimumab have shown encouraging efficacy. Nonetheless, therapeutic resistance remains a challenge, often driven by the immunosuppressive tumor microenvironment. Emerging strategies, such as next-generation checkpoint blockades, adoptive cell therapy, therapeutic cancer vaccines, and oncolytic virotherapy, are under investigation to improve response rates. This review discusses current progress in immunotherapy for HCC, addresses clinical limitations, and explores potential future directions to enhance treatment success.